Social Protection in Mozambique: A new imperative? - Waterhouse, Dr Rachel; Lauriciano, Gil (2009)
Even before the impact of a global economic crisis kicks in, there is renewed thinking in Mozambique about a wider role for the state in social protection. Proponents are still struggling to convince others of the economic and social value of a broader investment in social protection. This is against the backdrop of institutional resistance borne of Mozambique’s political and economic history. The government attitude to social protection has been influenced by colonial experience of an extractive rather than protective state and the legacy of post-Independence events and processes. After Independence in 1975, initial social service expansion was heavily undermined by war-time destruction and economic collapse in the 1980s. Post war, the Government’s top priorities were to re-establish security and rebuild infrastructure. However, political and economic liberalisation in the 1990s saw tight caps on state spending. Poverty was so widespread and deep that there seemed to be little scope for special consideration of the ‘poorest of the poor’... except for ad hoc initiatives, such as the food subsidy programme for the poor and unable to work. In the last 15 years, Mozambique has experienced impressive economic growth and poverty reduction. Nonetheless Mozambique continues to rank amongst the world’s poorest countries. Government is becoming more aware of chronic poverty and that large population groups are currently unable to escape the poverty trap. This raises debate about what can be done ... and promotes renewed thinking on social protection. There are still many obstacles to a coherent and comprehensive approach to social protection. These include: analytical limitations around the causes, consequences and extent of vulnerability as well as the potential social and economic benefits of social protection; institutional barriers; budgetary limitations; and perceived political risk. However, there is also a growing acceptance of the relevance and importance of social protection to reduce vulnerability, build resilience and contribute to poverty reduction. These issues need to be addressed at policy and practical level, if Mozambique is to effectively address the growing challenge of chronic poverty.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; poverty / pobreza; social protection / proteção social

Contexto Politico e institucional da protecao social em Mocambique - Waterhouse, Rachel; Lauriciano, Gil (Protecção Social: Abordagens, Desafios e Experiências para Moçambique, 2009)
Mesmo antes de se fazer sentir o impacto duma crise económica global, há um pensamento renovado em Moçambique sobre um papel mais amplo do Estado na protecção social. Os proponentes lutam de modo a convencer os outros do valor económico e social dum investimento mais alargado na protecção social. Isto vai contra o pano de fundo da resistência institucional, que a história política e económica de Moçambique acarreta. Moçambique já era unido como uma nação sob o regime colonial português, desde o princípio do século XX. O governo colonial praticou um regime altamente extractivo, fornecendo pouco para o bem-estar social ou a para a protecção social. Um breve período de políticas marxistas-leninistas após a independência nacional em 1975 –quando o governo da Frelimo tentou ampliar os serviços sociais básicos em todo o país– foi rapidamente superado pelo colapso económico e pela guerra, seguido por um rígido exercício de poder pelo estado sob ajustamento estrutural. Um pensamento renovado coerente e abrangente sobre um papel mais amplo do Estado no fornecimento duma Protecção social dos seus cidadãos é ainda emergente e controverso. Este artigo apresenta uma breve panorâmica do contexto político e institucional em que este debate está a ganhar importância.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; social protection / proteção social